Law No. 12/1996 enacting the Child Law. (2025)
Law No. 12 of The Year 1996 Enacting The Child Law PART-1: General Provisions. -- PART-2 : Health Welfare of The Child - Chapter - 1 : Practicing The Obstetric Profession. - Chapter - 2 : Registration of Newborn Children. - Chapter - 3 : Vaccination And Immunization of The Child. - Chapter - 4 : Health Care of The Child. - Chapter - 5 : Child's Food. -- PART - 3: Social Welfare - Chapter - 1: Nurseries. - Chapter - 2 : Surrogate Care. - Chapter - 3 : Protection From Traffic Dangers. -- PART - 4: Child Education - Chapter – 1 - : Chapter - 2 : Kindergartens. - Chapter - 3 : Stages of Education. - PART -5: Working Child And Working Mother Care - Chapter -1 : Working Child Care. - Chapter -2 : Working Mother Care. -- PART - 6: Handicapped Child Care And Rehabilitation. -- PART -7: Child Culture. -- PART -8: Criminal Treatment for Children. -- PART - 9: National Council for Childhood and Maternity.